Penatalaksanaan Holistik Penyakit Paru Obstruktif Kronik pada Lansia dengan Riwayat Merokok dan Paparan Polusi Udara - Riska Permata Sari; Diana Mayasari (CV. Jasa Sukses Abadi, 2020)
The Diseases that frequently affect elderly groups includes chronic degenerative diseases such as chronic obstructive pulmonary disease (COPD). Chronic Obstructive Pulmonary Disease (COPD) is a disease characterized by obstruction of air flow in the airways that is not completely reversible. This study aims to identify risk factors, clinical problems, and provide management of patients with the implementation of a holistic family physician services based on evidence based medicine approach to patient and family centered approach. This study is a case report. Primary data were obtained through history taking (directly from the patient and indirectly from family members), physical examination and a home visit to complete the family, psychosocial and environmental data. Secondary data were obtained from medical records of the patient at the health center. Assessment was made based on a holistic diagnosis from the beginning, process, and the end of quantitative and qualitative studies. 64-year-old male patient was diagnosed with COPD, He was worried his diseases can disturbing his activity. Patients do not have enough knowledge of the disease they are suffering from, have a habit of smoking 10-15 cigarettes per day and often exposed to air pollution when going to work and back home. Pharmacological and non-pharmacological interventions were carried out for patient and his families with education related to the patient's disease and exercises for respiratory muscles. In the evaluation found an increase in patient compliance to avoid risk factors and family knowledge about the disease and the existence of support in carrying out breathing exercises in patients. Services with a family medicine approach in pharmacological and nonpharmacological therapy are able to solve health problems and improve the quality of life of patients.